Infection of BHK-21 cells cultivated in stationary monolayers by PV and CVS strains - Mendes Batista, Alexandre (2009)
The rabies virus can be present in different tissues and organs, so it makes possible its replication in a wide variety of cells cultures. Because of the critical importance of virus production in vitro to achievement of diagnostic tests, production of hyperimmune sera and researches, the aim of this study was evaluate the viral replication of strains PV (Pasteur Virus) and CVS (Challenge Virus Standard) in cells lines BHK-21 (Baby Hamster Kidney). The cells were infected with strains PV and CVS and cultivated on stationary cell culture flasks and on microplates with cover glass slides on 37°C until 96 hours. Every 3 hours aliquots of supernatant were collected of the flasks for monitoring the virus particles concentration and glass cover to evaluate viral infection in cells. The evaluations were performed by direct immunofluorescence, to determinate the higher dilution that the viral suspensions infected 100% of the BHK-21 confluent monolayer and to evaluate the increase of fluorescence intensity, express by crosses (+ to ++++), identifying the viral antigen demonstrated by photos. The presence of viral particles was observed from 9 hours post-infection with both strains. The viral particles of CVS and PV strains on supernatant were obtained from 15 and 18 hours of incubation, respectively and the higher concentration of particles on viral suspensions was observed 72 hours post-infection. Therefore, the protocol used demonstrated efficiency independent of viral strain used allowing the obtaining of good titers in viral suspensions produced.